GROBNIČKI PEKTORALNI PRIVJESCI U KONTEKSTU ŽELJEZNODOBNE ESTETIKE SIMBOLA. - KAVUR, Martina BLEČIĆ (Histria Archaeologica, 2018)
Objects, especially decorative ones, play a central role in the mediation of heterogeneous social identities and their dimensions, and jewellery and adornment were, in a way, a symbolical representation of consciousness, thoughts, and form of existence. In the (non)verbal communication of the Iron Age social structures, the aesthetics of decorating oneself with symbolic jewellery has always served as a mediator of social, ideological, and religious concepts within their narrow community and within more widely accepted trends. The pectoral pendants from Grobnik are conceptually well-designed and artfully presented, and therefore, as a medium of a specific metaphorical message, they are interesting and suitable for new studies and various new understandings. This article, therefore, elaborates on the typological-stylistic analysis, iconographic syntax, comparison, and, where possible, the archaeological context of the pendants, for their better chronological positioning at the end of the Early Iron Age. Although their art expression is essentially reduced to a sign/symbol, semantically speaking, they were extremely powerful. As amulets, talismans, or good luck charms, despite often being rather sketchy and in a fragmented state, they mediated between the present and the past, shaping identities through their physical and metaphysical circulation, which is why their interpretation is presented from different aspects, and with a wider understanding of the Iron Age symbol aesthetics.